(untitled) (SAARC Journal of Agriculture, 2017)
This study was undertaken for the evaluation of existing animal slaughter and meat quality control act 2011 and way forward to its development in Bangladesh. Published data, SWOT analyses, structured questionnaires survey, Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) were carried out for critical analyses and explore the different stakeholders views. The study was carried out in seven divisions of Bangladesh namely Dhaka, Chittagong, Rajshahi, Khulna, Sylhet, Barisal and Rangpur. Total 285 representative samples (covering all stakeholders like farmers, butchers, meat processors, ULO/VS/PDO) were interviewed. Four FGDs and 50 KIIs were administered with different stakeholders. Descriptive statistics like percentage, mean, ranks and Binary logistic regression and Z test were used for data analyses. Findings show that the authority is not functioning properly due to lack of action plan and monitoring cell. Lack of certification authority, sanitary and meat inspector visit, restricted day, pre-slaughter and post-slaughter examination is visible. Act should be updated time to time to address the field based need. The study reveals that to implement the slaughter act Department of Livestock Services (DLS) as authority should have action plan and monitoring cell. SAARC J. Agri., 15(1): 111-122 (2017)